The Network and Dual Band (The Vortex), Nahjul Balagha As A Model - Abboud , Ashwaq Baqir Mohsen; Mahdi, Iman Matar (Journal of Ecohumanism, 2024)
Fokoniai and Turner’s (conceptual blending) theory is:A basic cognitive process that takes place according to a specific plan at different levels of abstraction.whata jobIn the intricately invisible side; not humanI am aware ofYoursNodules ofMHidden , AndSubtractThe two worlds Conceptual integration network idea It is a set of mental spaces through which conceptual blending processes unfold; depending on which organizational frames or relevant elements are projected into the blending space from the input spaces and which of them is dominant,And it isThere are four types of integration networks: (simple network, single-band network, mirror network, and dual-band network).